Physical Map of the DNA Genome of Autographa californica Nuclear Polyhedrosis Virus - Miller, Lois K. (1979)
A physical map of the 88 × 10(6) dalton, circular DNA genome of Autographa californica nuclear polyhedrosis virus was constructed. The complete order of BamHI and XmaI restriction enzyme sites was determined. The EcoRI and HindIII fragments were partially ordered, and their general locations, relative to the BamHI and XmaI maps, were determined. Alterations in the restriction endonuclease fragment patterns of natural genotypic variants of A. californica nuclear polyhedrosis virus, including Trichoplusia ni MEV nuclear polyhedrosis virus, were located on the physical map. Alterations were found throughout the A. californica nuclear polyhedrosis virus DNA genome.